Cochlear implant programme report in Dr. Soetomo Hospital Surabaya - Haris Mayagung Ekorini (PERHATI-KL, 2016)
Background: Cochlear implant is a result of technology development which has a great contributionto bilateral sensorineural hearing loss patients when conventional hearing aid does not help or does notgive enough benefit for these patients. In Surabaya, this program was started in November 2008.Purpose:To report cochlear implant programme in Dr. Soetomo Hospital Surabaya between November 2008 andOctober 2013.Methods: A descriptive retrospective study on complete data from medical record in Dr.Soetomo Hospital Surabaya between November 2008 and October 2013 were evaluated. Forty sevenpatients received cochlear implant, 3 patients did not have complete medical record and excluded, 44data were reviewed.Results: Forty four patients were implanted, the average of age identification was22.9 months old, the average of age of amplification was 29.7 months old and the average of age ofimplantation was 49.0 months old. All of the patients were prelingually deaf. Twenty seven patiens couldbe evaluated for habilitation with Categories of Auditory Performance (CAP) and the result of receptive,language, expressive and communication abilites were in good progress.Conclusion: The sooner thedevice implanted the better, and evaluation with CAP was effective. Keywords : Hearing impairment, cochlear implant, habilitation ABSTRAKLatar belakang: Implan koklea adalah hasil suatu perkembangan teknologi yang mempunyaikontribusi besar untuk pasien gangguan pendengaran sensorineural yang tidak bisa dibantu oleh alatbantu dengar. Di Surabaya, program ini dimulai pada November 2008. Tujuan: Evaluasi hasil programimplan koklea di RSUD Dr. Soetomo Surabaya sejak November 2008 sampai dengan Oktober 2013.Metode: Penelitian deskriptif retrospektif dan data diambil dari rekam medik yang lengkap di poliAudiologi RSUD Dr. Soetomo selama periode November 2008 sampai dengan Oktober 2013. Dari 47pasien yang dioperasi, 3 rekam medik tidak lengkap dan dieksklusi, 44 pasien yang mempunyai rekammedik lengkap dievaluasi. Hasil: Empat puluh empat pasien yang dilakukan implan koklea, rerataumur identifikasi 22,9 bulan, rerata umur amplifikasi 29,7 bulan, dan rerata umur operasi 49,0 bulan.Semua pasien adalah tuli sensorineural pre-lingual. Sebanyak 27 pasien dapat dilakukan evaluasihabilitasi dengan Categories of Auditory Performance (CAP) dengan hasil receptive, bahasa, ekspresifdan kemampuan berkomunikasi baik. Kesimpulan: Semakin muda umur pasien saat operasi hasilnyasemakin baik, dan evaluasi dengan CAP sangat efektif. Kata kunci: Gangguan pendengaran, implan koklea, habilitasi Correspondence: Haris M. Ekorini, Otorhinolaryngology Department, Faculty of Medicine AirlanggaUniversity/Dr. Soetomo Hospital, Surabaya. E-mail: hmekorini@yahoo.com.